logo for solving-math-problems.com
leftimage for solving-math-problems.com

algebra - equation with fractions











































Solve the fractional algebraic equation for x:

((1/2)x) - 2(x-1) = 2 - ((3/2)x)

show all steps and check your work

Comments for algebra - equation with fractions

Click here to add your own comments

Feb 04, 2011
Algebra - Equation with Fractions
by: Staff

The question:

((1/2)x)-2(x-1)=2-((3/2)x)


The answer:

((1/2)x) - 2(x - 1) = 2 - ((3/2)x)

((1/2)x) - 2x + 2 = 2 - ((3/2)x)

((1/2)x) - 2x + 2 – 2 = 2 - 2 - ((3/2)x)

((1/2)x) - 2x + 0 = 0 - ((3/2)x)

((1/2)x) - 2x = ((3/2)x)

2*[((1/2)x) - 2x] = 2*[((3/2)x)]

x - 4x = 3x

-3x = 3x

-3x + 3x = 3x + 3x

0 = 6x

0/6 = 6x/6

0 = x

The final answer: x = 0


The next step is to check the work. Substitute 0 for x in the original equation.

((1/2)x) - 2(x - 1) = 2 - ((3/2)x)

((1/2)*0) - 2(0 - 1) = 2 - ((3/2)*0)

0 +2 = 2 - 0

2 = 2

Since 2 does = 2, the equation is in balance. x = 0 is the correct answer.




Thanks for writing.


Staff
www.solving-math-problems.com


Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com